Pengaruh Kompetensi Komunikasi Hati dan Dukungan Sosial Teman Sebaya Terhadap Resiliensi Akademik Mahasiswa Tingkat Akhir - Handayani, Tusti; Lestari, Puji (Fakultas Ilmu Komunikasi UKWMS, 2025)
Final-year students often face complex academic pressures. Academic resilience is a key competency for students to be able to face pressure. Academic resilience is influenced by internal factors such as heart communication competency and external factors such as peer social support. The study aims to analyze the effect of heart communication competency (X1) and social support (X2) on the academic resilience of final-year students (Y). The study used a quantitative method. The research sample was 80 final-year students of the Faculty of Vocational Studies, UNY. Data collection through surveys to samples. Data analysis with parametric statistics in the form of linearity tests and hypothesis tests through simple correlation analysis methods, multiple correlation analysis, and multiple regression analysis. The results of the study showed that there was a positive and significant partial influence between X1 and Y of 40.2%, there was a positive and significant influence between X2 and Y of 26.5%, and there was a positive and significant influence together between heart communication competency and peer social support of 30.2% on academic resilience in students of the Faculty of Vocational Studies, UNY. The findings show that the competence of heart communication, with the dimensions of thinking, feeling, managing heart waste, sympathy, empathy, peace, and happiness, plays a dominant role in the academic resilience of final-year students. The contribution of the research provides a new understanding of the importance of heart communication competence and peer social support in supporting the academic resilience of final-year students. The results of the study support the Theory of Heart Communication, which emphasizes that thinking, feeling, managing heart waste, sympathy, and empathy for a peaceful and happy life can positively increase the academic resilience of final-year students. The study successfully tested the relevance of the Theory of Heart Communication to the academic resilience of final-year students at the Faculty of Vocational Studies, UNY, as a novelty. ABSTRAK Mahasiswa tingkat akhir kerap menghadapi tekanan akademik yang kompleks. Resiliensi akademik menjadi kompetensi kunci agar mahasiswa mampu menghadapi tekanan. Resiliensi akademik dipengaruhi faktor internal seperti kompetensi komunikasi hati dan eksternal seperti dukungan sosial teman sebaya. Penelitian bertujuan untuk menganalisis pengaruh kompetensi komunikasi hati (X1) dan dukungan sosial (X2) terhadap resiliensi akademik mahasiswa tingkat akhir (Y). Penelitian menggunakan metode kuantitaif. Sampel penelitian sebanyak 80 mahasiswa tingkat akhir Fakultas Vokasi UNY. Pengumpulan data melalui survei kepada sampel. Analisis data dengan statistik parametris berupa uji linearitas dan uji hipotesis melalui metode analisis korelasi sederhana, analisis korelasi berganda dan analisis regresi berganda. Hasil penelitian menunjukkan terdapat pengaruh positif dan signifikan secara parsial antara X1 dengan Y sebesar 40,2%, terdapat pengaruh positif dan signifikan antara X2 dengan Y sebesar 26,5%, dan terdapat pengaruh positif dan signifikan secara bersama-sama antara kompetensi komunikasi hati dan dukungan sosial teman sebaya sebesar 30,2% terhadap resiliensi akademik pada mahasiswa Fakultas Vokasi UNY. Temuan menunjukkan kompetensi komunikasi hati, dengan dimensi olah pikir, olah rasa, kelola sampah hati, simpati, empati, damai, dan bahagia berperan dominan terhadap resiliensi akademik mahasiswa tingkat akhir. Kontribusi penelitian memberikan pemahaman baru pentingnya kompetensi komunikasi hati dan dukungan sosial teman sebaya dalam mendukung resiliensi akademik mahasiswa tingkat akhir. Hasil penelitian mendukung Teori Komunikasi Hati yang menekankan bahwa olah pikir olah rasa, kelola sampah hati, simpati, empati, untuk hidup damai dan bahagia secara positif dapat meningkatkan resiliensi akademik mahasiswa tingkat akhir. Penelitian berhasil menguji relevansi Teori Komunikasi Hati terhadap resiliensi akademik mahasiswa tingakt akhir di Fakultas Vokasi UNY sebagai novelty.